Electrical reaistivity of amorphous Zr70 Cu30 and the Kondo like model - Guimpel, J. J.; Cruz, Francisco de la; Guimpel, Julio (Pergamon Press Ltd., 1982)
Fil: Guimpel, J. J. Comisión Nacional de Energía Atómica; Argentina